Region-specific heterogeneity in neuronal nuclear morphology in young, aged and in Alzheimer’s disease mouse brains - Das, Soumen; Ramanan, Narendrakumar (Frontiers in Cell and Developmental Biology, 2023)
Neurons in the mammalian brain exhibit enormous structural and functional diversity across different brain regions. Compared to our understanding of the morphological diversity of neurons, very little is known about the heterogeneity of neuronal nuclear morphology and how nuclear size changes in aging and diseased brains. Here, we report that the neuronal cell nucleus displays differences in area, perimeter, and circularity across different anatomical regions in the mouse brain. The pyramidal neurons of the hippocampal CA3 region exhibited the largest area whereas the striatal neuronal nuclei were the smallest. These nuclear size parameters also exhibited dichotomous changes with age across brain regions – while the neocortical and striatal neurons showed a decrease in nuclear area and perimeter, the CA3 neurons showed an increase with age. The nucleus of parvalbumin- and calbindin-positive interneurons had comparable morphological features but exhibited differences between brain regions. In the context of activity-dependent transcription in response to a novel environment, there was a decrease in nuclear size and circularity in c-Fos expressing neurons in the somatosensory cortex and hippocampal CA1 and CA3. In an APP/PS1 mutant mouse model of Alzheimer’s disease (AD), the neuronal nuclear morphology varies with plaque size and with increasing distance from the plaque. The neuronal nuclear morphology in the immediate vicinity of the plaque was independent of the plaque size and the morphology tends to change away from the plaque. These changes in the neuronal nuclear size and shape at different ages and in AD may be attributed to changes in transcriptional activity. This study provides a detailed report on the differences that exist between neurons in nuclear morphology and can serve as a basis for future studies.